Analisis Teoritis Tragedi Kanjuhuran Malang: Telaah Manajemen Qolbu Aa Gym Dan Al Ghazali Serta Pengendalian Diri Hurlock: Theoretical Analysis of the Malang Kanjuhuran Tragedy: Study of Qolbu Aa Gym and Al Ghazali Management and Hurlock's Self-Control - Andriani; Muhamad Sophian; Ilyas Adhi Purba (Sociocouns: Journal of Islamic Guidance and Counseling, 2023)
At the beginning of October 2022, it became one of the dark history for the world of sports, especially in Indonesian football. The incident that occurred at the Kanjuhuran Stadium in Malang, when Persebaya played against Arema FC. The riots claimed the lives of more than a hundred people. According to some news, that the shooting of tear gas and the locked stadium doors made supporters die. Researchers are interested in studying the management of the hearts parties involved during the incident, in case the management of the heart before doing something. In addition, the study aims analyze concept an individual's self-control according to Hurlock's theory. Through descriptive qualitative approach, which to describe the condition object and theoretical analysis. The results of this study explain that according the management of qolbu Aa Gym, in addressing problem not good to do with violence, emotionally and selfishly. In addition, managing heart can be through remembrance, thought, and endeavor. Meanwhile, according the philosopher, Al Ghazali stated that heart is like kingdom there is part that regulates one's behavior. In addition, Al Ghazali also emphasizes staying away from lust not to become an enemy in oneself. Based on Hurlock's self-control method, the factors that can affect of controlling himself age and family environment. So as adults, of course, they can control themselves, and the important role of parents in teaching events occur for children's lives the future. Hurlock's method of self-control includes behavioral control, cognitive control, decision control, information control, and retrospect control.